Answer:
(-1, 1)
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
- Equality Properties
<u>Algebra I</u>
- Solving systems of equations using substitution/elimination
- Solving systems of equations by graphing
Step-by-step explanation:
<u>Step 1: Define systems</u>
3 + 2x - y = 0
-3 - 7y = 10x
<u>Step 2: Rewrite systems</u>
3 + 2x - y = 0
- Add <em>y</em> to both sides: 3 + 2x = y
<u>Step 3: Redefine systems</u>
y = 2x + 3
-3 - 7y = 10x
<u>Step 4: Solve for </u><em><u>x</u></em>
<em>Substitution</em>
- Substitute in <em>y</em>: -3 - 7(2x + 3) = 10x
- Distribute -7: -3 - 14x - 21 = 10x
- Combine like terms: -14x - 24 = 10x
- Add 14x on both sides: -24 = 24x
- Divide 24 on both sides: -1 = x
- Rewrite: x = -1
<u>Step 5: Solve for </u><em><u>y</u></em>
- Define original equation: -3 - 7y = 10x
- Substitute in <em>x</em>: -3 - 7y = 10(-1)
- Multiply: -3 - 7y = -10
- Add 3 to both sides: -7y = -7
- Divide -7 on both sides: y = 1
<u>Step 6: Graph</u>
<em>Check the solution set.</em>
605 pounds is 840.25 dollars
405 dollars is 313.30 pounds
Answer:
2, 5, 9, 19
Step-by-step explanation:
Using the recursive formula f(n) = 2f(n - 2) + f(n - 1)
with f(1) = 2 and f(2) = 5
f(3) = 2f(3 - 2) + f(3 - 1)
= 2f(1) + f(2) = (2 × 2) + 5 = 4 + 5 = 9
f(4) = 2f(4 - 2) + f(4 - 1)
= 2f(2) + f(3) = (2 × 5) + 9 = 10 + 9 = 19
Answer:
Step-by-step explanation:
3x - 4y = 13 (1)
2x + y = 5 (2)
——————
3x - 4y = 13
4(2x + y = 5) (2) times 4
——————-
3x - 4y = 13
8x + 4y = 20
——————-
11x = 33
x = 33/11
x = 3
Plug x = 3 in (2):
2(3) + y = 5
6 + y = 5
y = 5-6
y = -1
Thus, x = 3 and y = -1
0.001)) milli to grams is x 1000